Bacterial spore formers : (Brooks Cole / Thomson Learning, 2004)
Biologists in various specialties, but mostly microbiology, from Europe, North America, Japan, and Thailand remind laboratory scientists that the bacteria they study under controlled conditions behave differently in their own natural settings. They concentrate on members of the genus Bacillus and related genera, which are capable of producing a type of resting cell called endospore that can survive extremes of time and environment. Their topics include the ubiquity, longevity, and ecological roles of the spores; the ecology of Bacillus species in soil; the safety of the bacteria; the spores as probiotic products for human use; the display of molecules on the spore surface; and European Union regulations on bacillary probiotics for animal feeds. Distributed in the US by Taylor and Francis.